Variations of internal structure and moisture distribution in activated sludge with stratified extracellular polymeric substances extraction - Yuan, Dongqin; Wang, Yili; Qian, Xu (International biodeterioration & biodegradation, 2017)
The floc rupture and fractal structure during the ultrasonic pretreatment, rheological parameters as well as bound water content of activated sludge before/after extracellular polymeric substances (EPS) extraction was investigated to examine the variations of internal structure and moisture distribution in activated sludge with stratified EPS extraction. It was observed that the floc disruption was dominated by the model of large-scale fragmentation initially and by smaller-scale surface erosion subsequently for activated sludge before/after EPS extraction. Activated sludge with tightly bound EPS (TB-EPS) showed greater mass fractal dimension (Df) and rheological parameters hysteresis loop area, limiting viscosity (η∞), yield stress (τy), energy of cohesion of network structure (Ec) and shear modulus (G) than the other sludge samples, indicating that activated sludge after loosely bound EPS (LB-EPS) extraction exhibited a denser and stronger network structure. A water classification is also proposed: free water (bulk water and some portion of interstitial water) and bound water (osmotic, surface and intracellular water). The osmotic water (interstitial-bound water) in the LB-EPS fraction (4.3% of the total water content) exhibited much more than that in the TB-EPS (0.2% of the total water content). Bound water (surface and intracellular water) in the TB-EPS and Pellet comes to be the subject to be treated after mechanical dewatering. [Display omitted] •Tightly bound extracellular polymeric substances (TB-EPS) were the key part.•Floc rupture model varied after 60 s of sonication for activated sludge with TB-EPS.•Activated sludge with TB-EPS exhibited a denser and stronger network structure.•Surface and intracellular water in the TB-EPS and Pellet needs further dewatering.